PENGARUH VIDEO PEMBELAJARAN TERHADAP MOTIVASI BELAJAR BAHASA INGGRIS DI TK AL-AZHAR 21 PONTIANAK - Sukamto, Rinda Nikenindiana; Aunurrahman, Aunurrahman; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to know the influence of video for the students of Al-Azhar 21 Pontianak in motivate learning Englihs. This research used  kuantitatif approachment, the method is true eksperiment. The design is pretest-posttest group design. The first sampel are B1 class it have 19 students as the eksperimen group the second, B3 class have 19 students as the control group. technique of collecting data are observation and documentation. The teaching of analisis data is descriptive by look at average and t test for the result of presentation. Based on analysis data about the influence of video in motivate learning English for the students in 5-6 years old by compare eksperimentaland control groups show t count is 4,388. The valve of the test by significant level is 5% for one side and 0,025 for two side freedom of learning is 36 obtailable 2,028, hypothesis is denied because of tcont>ttabel (4,388>2,028). That means has the influence by using video in teaching English the determinat koefisien is 34,81% show the influence in teaching for Al-Azhar 21 Pontianak students. The conclusion of this research is video learning has the influence in motivated students in teaching English for kids.    Keywords: Video, English, Motivation Learning.